Perkembangan Usaha Agribisnis Bunga Anggrek Vanda Potong pada Kembang Batur Anggrek Collection di Desa Sanur Kaja Denpasar - YANTI, LIZA PRISKA NOVI; SUAMBA, I KETUT; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
The Business Growth of Cut Orchid Vanda Flower in Kembang Batur Anggrek Collection at Desa Sanur Kaja Denpasar Timur, Denpasar-Bali Increasing number of flowrist at Denpasar City make every company must have more value to attract consumers. Kembang Batur Anggrek Collection is one of the flowrist that supply consumer’s need at Denpasar. The purpose of the study to determine how the business growth of cut orchid Vanda flower observed form profit, volume of sales, and constraints in Kembang Batur Anggrek Collection. The results of this study shows profit growth in the TR calculation is Rp 5.831.500.000,00 ; the TC calculation is Rp 3.704.811.000,00 and the calculation profit obtained is Rp 2.126.689.000 over ten years. The average business profits of cut orchid Vanda flower in Kembang Batur Anggrek Collection is Rp 212.668.900,00 every year and the sales volume of the annual accounts showed an increasing sales. The cultivation of Cut Orchid Vanda Flower in Kembang Batur Anggrek Collection should be continued and developed with effort leads to an increase in the number of production. In order to fulfill the increasing market demand of Cut Orchid Vanda Flower.